2023
DOI: 10.1111/1346-8138.16732
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving microneedles for effective and painless intradermal drug delivery in various skin conditions: A systematic review

Abstract: Intra-and transdermal drug delivery via the skin offers a non-to minimally-invasive, effective, and patient-compliant method for administrating substances such as medication or vaccines. 1-3 Intra-and transdermal delivery is considered profoundly safe, maintains a steady plasma concentration and avoids the significant hepatic first-pass metabolism effect which limits the biological availability in enteral administration. [1][2][3][4] Parenteral administration via cutaneous penetration is considered to be painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In our previous study, De Decker et al. successfully applied 0.89 mg/cm 2 corticosteroid-loaded hyaluronic acid patches on hypertrophic wounds in a 4-month pilot study (De Decker et al., 2023c ). However, the HA-based MN arrays applied in the pilot study consisted of 320 MNs, whereas the currently developed MN arrays consisted of 36 individual MNs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, De Decker et al. successfully applied 0.89 mg/cm 2 corticosteroid-loaded hyaluronic acid patches on hypertrophic wounds in a 4-month pilot study (De Decker et al., 2023c ). However, the HA-based MN arrays applied in the pilot study consisted of 320 MNs, whereas the currently developed MN arrays consisted of 36 individual MNs.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the mechanical properties, compression testing was performed on a universal testing machine (Tinius Olsen) equipped with a 25 N load cell at room temperature (De Decker et al., 2023c ). The preload was set at 0.1 N, and the speed of the compression was set at 0.5 mm/min until 20 N load was reached.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By momentarily disturbing the skin’s surface layer, the microneedle delivery device uses the diffusion process to transfer the medicine through the skin. On a tiny patch, hundreds of microneedles are organized to help distribute enough medication to have a therapeutic impact. , The trilayer dissolving microneedle array (RBTF-TDMNs) was created to maximize the intradermal administration of RBTF for the treatment of melanoma. It has been demonstrated that RBTF-TDMNs are powerful enough to penetrate excised porcine skin while keeping their physicochemical qualities, quickly disintegrate, and deposit RBTF intradermally.…”
Section: Other Nanocarriers For Topical Drug Deliverymentioning
confidence: 99%